THE EFFECTS OF PHYSICS LEARNING WITH STARTER EXPERIMENT APPROACH (SEA) TO IMPROVE STUDENT LEARNING OUTCOMES - Faradiba, Faradiba; Sakatsila, Dedi Juliasman; Sianturi, Manogari (International Journal of Educational Management and Innovation, 2020)
According to regulation No. 20/2000, education is a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential, to have spiritual strength, self-control, personality, intelligence, noble character and the skills needed by themselves, society, nation, and country. To realize this we need learning methods and models that are able to increase student enthusiasm and be able to improve student learning outcomes. Of the several learning approaches, the initial experiment approach (starter experiment approach), is one alternative in learning physics. This research was conducted in class XI Natural Sciences at SMA Negeri 98 Jakarta, East Jakarta, with a research schedule from January to September 2018. The results showed that the average posttest score of the experimental class students after receiving the SEA learning model treatment was 87.38, while the class control with conventional learning models 80.36.